2007
DOI: 10.1111/j.1742-4658.2007.05806.x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane trafficking of CD98 and its ligand galectin 3 in BeWo cells − implication for placental cell fusion

Abstract: CD98 heavy chain (CD98hc), expressed at high levels in developing human trophoblasts, is an integral membrane protein with multiple N‐linked glycosylation sites and known to be important for cell fusion, adhesion, and amino acid transport. Western blotting and flow cytometry were used to study the effect of brefeldin A, an inhibitor of protein translocation through the Golgi, on CD98hc in the human placental trophoblast cell line BeWo. Although brefeldin A treatment caused increased cell surface expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 37 publications
3
36
0
Order By: Relevance
“…terminal SC-PNAL chains does not alter the overall protein mass (data not shown). Nonetheless, the presence of PNAL glycans on CD147 and CD98 proteins has been described in other studies (66,67). Our studies using TL also confirm PNAL on CD147 and CD98 proteins individually immunoprecipitated by Abs to CD147 or CD98, respectively, using protein-G (data not shown).…”
Section: Discussionsupporting
confidence: 88%
“…terminal SC-PNAL chains does not alter the overall protein mass (data not shown). Nonetheless, the presence of PNAL glycans on CD147 and CD98 proteins has been described in other studies (66,67). Our studies using TL also confirm PNAL on CD147 and CD98 proteins individually immunoprecipitated by Abs to CD147 or CD98, respectively, using protein-G (data not shown).…”
Section: Discussionsupporting
confidence: 88%
“…We therefore suggest that some common mechanisms involving 4F2hc underlie such physiological and pathological cell fusions. A previous study indicated that galectin-3, a member of lectin family, is a ligand for 4F2hc and binds to the extracellular domain of 4F2hc to promote BeWo cell fusion (6). In that study, based on the observation that lactose, a disaccharide ligand of galectin-3, interfered with the forskolin-induced cell fusion, galectin-3 was suggested to recognize N-linked sugar chains in the extracellular domain of 4F2hc.…”
Section: Discussionmentioning
confidence: 99%
“…Two retrovirusderived murine proteins, syncytins, have been identified to mediate syncytialization of trophoblastic cells in the developing placenta (3,4). Although the in vivo relevance has not been well addressed, several other proteins, including the single-membranespanning type II membrane glycoprotein 4F2hc/CD98hc/FRP-1, have been also suggested to be involved in the cell fusion of trophoblastic cells (5)(6)(7)(8)(9)(10)(11)(12). 4F2hc is the heavy chain subunit of 4F2 antigen (CD98) and is covalently linked to a nonglycosylated light chain.…”
mentioning
confidence: 99%
“…Independently, increased Gal-3 expression may also play a special role in tissue remodeling because of its adhesive and growth-regulative effects (Pricci et al, 2000). CD98, known to be important for cell fusion, adhesion, and amino acid transport, is also a demonstrated receptor for Gal-3 (Dong and Hughes, 1997;Dalton et al, 2007). The mechanistic link among interleukin (IL)-4, Gal-3, and CD98 can drive alternative macrophage activation and chronic inflammatory and fibrotic diseases (Dong and Hughes, 1997).…”
Section: Cell Receptors and Ligandsmentioning
confidence: 99%